Rapid Improvement in Visual Selective Attention Related to Action Video Gaming Experience - Qiu, Nan; Ma, Weiyi; Fan, Xin; Zhang, Youjin; Li, Yi; Yan, Yuening; Zhou, Zhongliang; Li, Fali; Gong, Diankun; Yao, Dezhong (Frontiers in Human Neuroscience, 2018)
A central issue in cognitive science is understanding how learning induces cognitive and neural plasticity, which helps illuminate the biological basis of learning. Research in the past few decades showed that action video gaming (AVG) offered new, important perspectives on learning-related cognitive and neural plasticity. However, it is still unclear whether cognitive and neural plasticity is observable after a brief AVG session. Using behavioral and electrophysiological measures, this study examined the plasticity of visual selective attention (VSA) associated with a one-hour AVG session. Both AVG experts and non-experts participated in this study. Their VSA was assessed prior to and after the AVG session. Within-group comparisons on the participants’ performance before and after the AVG session showed improvements in response time in both groups and modulations of electrophysiological measures in the non-experts. Furthermore, between-group comparisons showed that the experts had superior VSA, relative to the non-experts, prior to the AVG session. These findings suggested an association between the plasticity of VSA and AVG. Most importantly, this study showed that the plasticity of VSA was observable after even a one-hour AVG session.